IMPLEMENTASI YOUTUBE SHOPPING DALAM OPTIMALISASI MONETISASI PADA CHANNEL MNCTV OFFICIAL - Putri Ananta, Albina Sherly; Priatna, Wahyu Budi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of YouTube Shopping in optimizing monetization on the MNCTV Official YouTube channel. The research used a quantitative descriptive method by utilizing secondary data obtained from YouTube Studio Analytics and the YouTube Shopping dashboard during the period of March 1–31, 2026. The object of this study consisted of video content integrated with the YouTube Shopping feature through Product Tagging connected to e-commerce platforms. The results showed that the implementation of YouTube Shopping provided additional monetization opportunities through product sales commissions integrated into video content. During the research period, the total product sales reached Rp596,259 with an estimated revenue of Rp32,198. Drama and FTV content demonstrated the highest monetization performance due to high audience engagement and watch time. The contribution of YouTube Shopping to the total channel revenue reached 0.02%, indicating that although the contribution remains relatively small, the feature has potential as an alternative digital monetization strategy based on social commerce. The study concludes that YouTube Shopping can support media companies in diversifying digital revenue streams in the era of digital economy and social commerce development.